The Implementation of Hybrid Cultural Learning Through the Integration of Deep Learning and Problem-Based Learning to Enhance Students' Cultural Literacy - Prihma Sinta Utami; Wasis Suprapto; Trapsila Hutami; Velinsia Purnama Ojo (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2025)
This study examines the effectiveness of Hybrid Cultural Learning integrating Deep Learning and Problem-Based Learning (PBL) in enhancing students’ cultural literacy in an Educational Psychology course. A mixed-methods sequential explanatory design was employed with 72 students divided into experimental and control groups. Quantitative results indicate a significant improvement in cultural literacy in the experimental group (t = 7.842; p < 0.001), with mean scores increasing from 67.4 to 84.9, while the control group showed no significant change. Qualitative findings reveal that the integrated approach enhances contextual understanding, student participation, collaboration, and higher-order thinking skills (HOTS). Overall, the findings suggest that the integration of Hybrid Cultural Learning, Deep Learning, and PBL is effective in improving students’ cultural literacy in Educational Psychology learning.